Languishing in the crossroad? A scoping review of intersectional inequalities in mental health - Nadja Fagrell Trygg; Per E. Gustafsson; Anna Månsdotter (BMC, 2019)
Abstract The concept of intersectionality has gradually been introduced to health inequality research, adding depth and breadth to the way inequalities in health are approached. We conducted a scoping review with the purpose to systematically map, describe and analyze the literature about intersectional inequalities in mental health. For eligibility, the study had to analyze and report inequality defined by combinations of socioeconomic position, gender, race/ethnicity, sexual orientation or religion. The mental health outcome had to be measured as self-reported symptoms assessed through validated scales, or disorders assessed through diagnostic interviews. The search strategy was applied in two databases and the screening process yielded 20 studies. The interaction of intersectional positions showed no consistent patterns in mental health across studies, but both synergistic and antagonistic effects were observed. In most studies an absolute measure of inequality was used and few studies analyzed factors potentially explaining the intersectional inequalities. Taken together, the findings of this review highlight the value of assessing intersectional inequalities across population groups for priority setting and action on mental health inequalities.